The Practice of Entrepreneurship Education in a Malaysian Higher Education Institution: A Single Case Study - Nawawi, Atiqah; A. Samah, Narina; Osman, Sharifah; Jaffri, Hadijah (International Journal of Psychosocial Rehabilitation, 2020)
This study assessed the practice of entrepreneurship education in a Malaysian higher education institution (HEI). The teaching methods adopted by lecturers are integral in enhancing the quality of entrepreneurship education in Malaysia. As such, a single case study design was employed, in which a lecturer served as the purposive sampling. A semi-structured interview was conducted to generate qualitative data. Drawing on Arasti et al. [1]’s teaching methods in entrepreneurship education, concept-driven thematic analysis was performed. The study outcomes may serve as a reference and guidance to other academicians and stakeholders. This study is an effort to intensify interest among students towards entrepreneurship and is an excellent platform to embrace the idea of self-employment as an entrepreneur upon graduation.